Phosphate-solubilizing microorganisms for soil health and ecosystem sustainability: a forty-year scientometric analysis (1984–2024) - Lei, Yiming; Kuai, Yuhan; Guo, Mingyu; Zhang, Huan; Yuan, Yuan; Hong, Hualong (Frontiers in Microbiology, 2025)
Phosphate-solubilizing microorganisms (PSM) play a crucial role in promoting crop growth by enhancing phosphorus supply and reducing phosphorus loss in soil. However, a comprehensive bibliometric overview of the research landscape on PSM in agricultural applications has been lacking. This study conducts a bibliometric analysis to explore global research trends, key contributors, and collaborative networks in the application of PSM in ecological restoration, providing valuable insights for future research. A total of 1,662 documents from the Web of Science Core Collection, spanning from 1984 to 2024, were extracted and analyzed using Bibliometrix and CiteSpace software. The findings reveal a period of rapid growth in this field since 2018. Initially, research focused on microbial soil nutrients, such as phosphate rock and Azospirillum brasilense. Current research hotspots have shifted towards topics like drought and salt stress, as well as productivity, reflecting an increasing emphasis on mitigating the impacts of global warming and environmental changes. China and India lead in research output, contributing 36.67% of the total articles. The Indian Council of Agricultural Research published the highest number of articles. Future research on PSM should emphasize their role in enhancing nutrient uptake, improving soil health, and mitigating environmental stresses, supporting sustainable agriculture and ecological restoration. This bibliometric analysis of 1,162 articles by 7,454 authors from 101 countries highlights critical advances at the intersection of soil microbiology, sustainable land management, and climate change adaptation. These findings provide a foundation for addressing global challenges like soil degradation, nutrient cycling, and food security, aligning with the Sustainable Development Goals.